(3TQM GdcQGSIs - (3CHhGdMSf TgGH GdOjf CMeO Hf eMeO Hf eMeO GdHLGFj GdCHPjs; (3GHf jddHNJ , YjSi Hf YHO GdYRjR Hf jddHNJ GdLRhdj GdHQHQj GdeQGcTj, CHh ehSi,J (B607 (3g` s
(3ChdgG (B:s
(3HGH(B: (3gPG gh HGH MQha GdNaVi hZjQgG eeG jNaV hdfYW aj Pdc ebOeI s
(3BNQgG (B:s
(3hjecf Cf jchf GdJfhjf aj GdHjJ Jfhjf GdJQfe GdPj jdMb aj GdbhGaj YhVkG GfJgi cdGe T Je GdTQM s
(3GdfSNI ebGHdI Ydi CUd ebGHdI HCUd GdeDda YGe (B915(3g``s
(3HChdgG Jedc HJGQjN (B995(3g``s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddCHhGHs
(3HgG JbWjY aj ChQGbgG GdChdi hGdCNjQI s
(3bQf GdfSN (B:s
Keywords: (3GdfMhs